Análise económica e financeira a uma empresa do setor turístico - Gomes, Ana Rita da Cruz (2022)
The present paper materializes the work developed in the company DNI Consultores, Lda, through a curricular internship with a total extension of 600 hours distributed over seven months. This period of constant learning was carried out with the purpose of achieve the Master's degree in Accounting and Finance from the Instituto Superior de Contabilidade e Administração do Porto. This report contains an extensive analysis of a company in the tourism sector which was named EMPLíder, Lda. This study started with an economic and financial analysis, through the study of ratios, complemented by an evaluation of the company through the discounted cash flow model, and finalized with an evaluation of the risk of bankruptcy due to default through the Altman Z-Score model. The analysis was carried out using mainly accounting and tax information provided by the entity. The method used consisted of quantitative and qualitative techniques, adapted to the business scenario. Although the company's financial situation points to an unfavorable scenario, even indicating a possible difficulty in meeting its future commitments, it is important to note that the period of analysis covers two years in which tourism activity was strongly conditioned by the Covid-19 pandemic. The analysis concluded that although the company had been performing well above the industry average until 2019, the investments made in 2020 to increase its capacity did not bring returns for that year or the next because the company's activity was strongly conditioned by the successive lockdowns implemented in the country and the world in the period between 2020 and 2021. Despite this, the outlook for the year 2022 is for a marked recovery in tourism, at which time the company may significantly improve its economic and financial situation.